A Chemotaxonomic Study in the Genus Zingiber - MARSUSI MARSUSI; AHMAD DWI SETYAWAN; SHANTI LISTYAWATI (Society for Indonesian Biodiversity, 2001)
Zingiber is profitable for spice, ingredients, medicine and garnishing plant (Purseglove, 1972). The systematic ofZingiber (and other Zingiberaceae) has been argued among the authors, because they commonly use the morphological and the anatomical characters, that they obtain limited data. The chemical constituents of volatile oils are one of the most prospective characters for taxonomy of Zingiber. This research is objected to find out (1) the constituents of volatile oils (2) the number and the type of compounds composing volatile and (3) the genetic relationship. This research is done in the laboratory. The data seeking covers, i.e. (1) water distillation (Guenther, 1948; Anon, 1977), (2) extraction (Anon, 1977; Harborne, 1984), and gas chromatography (Mc Nair & Bonelli, 1968;Pramono, 1988). Dendrogram is arranged referring to Sokal & Sneath (1963), and the association coefficient degrees are determined referring to Pielou (1984). The rhizomes are gathered from Bogor Botanical Garden and from around Surakarta. There are seven achieved species, namely Z. amaricans Nor., Z. aromaticum Val., Z. cassumunar Roxb.,Z. gramineum Bl., Z. officinale Roxb., Z. ottensii Val., and Z. zerumbet (L.) J.E. Smith. Every species is identified referring to manuals of Backer & Bakhuizen van den Brink (1968), Holttum (1950) and Burkill (1935). The volatile contents of seven species subsequently are 4.67% (ml/100gr.), 5.00%, 6.33%, 0.20%, 6.67%, 4.29% and 6.00%. The numbers of composing volatile compounds subsequently are 30, 26, 37, 44, 29, 29 and 29. The genetic relationships of seven species are Z. amaricans, Z. aromaticum and Z. zerumbet joint at similarity index of 90, and it is followed by Z. ottensii at similarity index of 85. Then those five species join with Z. cassumunar and Z. gramineum at similarity index of 60. The last is the joining of Z. officinale to those six species at similarity index of 55.Â© 2001 Jurusan Biologi FMIPA UNS SurakartaKeywords: chemotaxonomy, volatile oils, Zingiber.